Faktor-faktor yang Mempengaruhi Kepuasan Orang Tua Siswa terhadap Layanan Pendidikan di Sekolah (Studi pada Sekolah Unggulan di Kabupaten Jombang) - Agus Prianto (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
Recently, public attention to the existence of the top schools is increasing. It appears from the growing amount of interest people who are interested to send her son to go to school. With the advantages facilities, excellent schools managed to convince the parents to pay tuition fees of a relatively large when compared with ordinary schools. Amount of tuition fees to be paid by the parents would insist on better service activities. This study would assess the degree of satisfaction of the parents towards education services at school. This research is to complete the studies conducted by Standifird, et.al. (2008), who examines the satisfaction of students. By using analyser statistics, that is structural equation modeling (SEM), this studies reveal that the school is expected by the parents to be more responsive to the desires, wishes and complaints of the parents. Accordingly, the parents also expect the school to have attentive and caring with the parents of students. School leaders are also expected to continue to express the importance of good educational service to the staff, a representative of school buildings, school supplies are sufficient, teachers and school staff are professionals in the field of work.Keywords: excellent school, school services, satisfaction of the parents